IMPROVING THE PROCESS AND LEARNING OUTCOMES IN MATHEMATICS THROUGH THE TALKING STICK MODEL ASSISTED BY PUZZLE MEDIA IN SECOND GRADE STUDENTS - Ida Linur Insan; Puput Wahyu Hidayat; Subhanadri Subhanadri (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
The objectives of this study are to determine: the learning process through the Talking Stick model assisted by puzzle media in Grade III of SDN 36/II Sarana Jaya, Bathin III Subdistrict, Bungo Regency; and the learning outcomes through the Talking Stick model assisted by puzzle media in Grade III of SDN 36/II Sarana Jaya, Bathin III Subdistrict, Bungo Regency. This study employed Classroom Action Research (CAR) as its method. The Classroom Action Research was conducted in Grade III at SDN 36/II Sarana Jaya, Bathin III Subdistrict, Muaro Bungo Regency. This research was carried out every Monday and Wednesday, from May 26, 2025, to June 4, 2025, during the even semester of the 2024/2025 academic year. The subjects of this study were third-grade students at SDN 36/II Sarana Jaya, Bathin III Subdistrict, Muaro Bungo Regency, totaling 25 students, in the subject of Mathematics. The object of this Classroom Action Research was the implementation of the Talking Stick learning model assisted by puzzle media to improve the learning process and learning outcomes in Mathematics for Grade III students at SDN 36/II Sarana Jaya. The research findings on of learning using the Talking Stick model assisted by puzzle media can improve the learning process. This was evident from the improvement in the teacher's teaching process in Cycle I, which reached a success rate of 78.94% and was categorized as "Good." Meanwhile, the success rate of the students' learning process was 48%, which fell under the "Less Good" category. In Cycle II, the teacher's teaching process improved significantly, reaching a success rate of 94.73% with a "Very Good" category. Similarly, the students' learning process also improved and was categorized as "Very Good" with a success rate of 88%. the Talking Stick model assisted by puzzle media in Mathematics can enhance students' learning outcomes. This was proven by the fact that prior to using the Talking Stick model with puzzle media, the learning mastery rate was only 44% (11 students). In Cycle I, this increased to 72% (18 students) who achieved the Minimum Mastery Criteria (KKTP). Therefore, the researcher proceeded to Cycle II, where the mastery level further improved to 92%. The actions implemented in Cycle II showed an increase and exceeded the predetermined mastery standard or success indicators.